Population Mobility, Urban Planning and Management in China - Wong, Tai-Chee; Han, Sun Sheng; Zhang, Hongmei (Springer International Publishing : Imprint: Springer, 2015)
This volume contains essays that examine contemporary urban and regional planning and development in China.  Through in-depth theoretical and empirical analysis, it provides insights into the urban policies and operational mechanisms of this colossal transitional economy which has presented unprecedented challenges and dynamics. Inside, readers will discover the causes and consequences of rapid urbanization that have led to a series of environmental, economic and social planning and management measures designed to achieve quality urban living. The essays also detail efforts in adopting the latest options in city building such as specific urban planning approaches in developing large city regions, building cities without slums, constructing new townships and green urbanism, including eco-city and sustainable transport. In addition, coverage explores financial management and support as a means to encourage urbanization and urban economic growth in less-developed regions. Overall, the volume offers a wealth of concrete, detailed information on conditions in different regions of China and features an extensive range of content, methods and theory. It provides readers with a comprehensive portrait of the chain relationship between rapid urbanization, spatial planning and management throughout the country. The book will serve as a useful reference for national and international consultancy services doing business or serving public interest in China. It will also be of interest  to an international audience seeking a better understanding of urban development and planning in China, including university teachers, students,  government agencies and general readers.